2011
DOI: 10.3109/08990220.2011.598268
|View full text |Cite
|
Sign up to set email alerts
|

Spinal cord excitability is not influenced by elevated blood lactate levels

Abstract: The aim of the present study was to examine the association of high blood lactate levels, induced with a maximal cycling or with an intravenous infusion, with spinal cord excitability. The study was carried out on 17 male athletes; all the subjects performed a maximal cycling test on a mechanically braked cycloergometer, while 6 of them were submitted to the intravenous infusion of a lactate solution (3 mg/kg in 1 min). Before the exercise or the injection, also at the end as well as 5 and 10 min after the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…This enhancement of M1 excitability strongly correlates with the increase of blood lactate and in the same study ) a similar effect on the M1 hand area was also observed when increasing the blood lactate levels by an intravenous infusion in resting participants. The same group suggested that lactate acts at the cortical level since they observed that the improvements in M1 excitability is not associated with changes of excitability of spinal (Coco et al 2011) or brain stem (Coco et al 2013a). Moreover, it has been recently observed in vitro that lactate may promote astroglial brain-derived neurotrophic factor expression related to an increase in heat shock protein 70 in adverse situations (Coco et al 2013b).…”
Section: Discussionmentioning
confidence: 94%
“…This enhancement of M1 excitability strongly correlates with the increase of blood lactate and in the same study ) a similar effect on the M1 hand area was also observed when increasing the blood lactate levels by an intravenous infusion in resting participants. The same group suggested that lactate acts at the cortical level since they observed that the improvements in M1 excitability is not associated with changes of excitability of spinal (Coco et al 2011) or brain stem (Coco et al 2013a). Moreover, it has been recently observed in vitro that lactate may promote astroglial brain-derived neurotrophic factor expression related to an increase in heat shock protein 70 in adverse situations (Coco et al 2013b).…”
Section: Discussionmentioning
confidence: 94%
“… 4 , 5 It has also been suggested that in the brain, in particular in conditions of altered energy production, such as anoxia or hypoglycemia, lactate is the energetic metabolite used for sustaining glutamatergic synaptic activity. 6 However, it has been observed that an increase of blood lactate, induced by an exhaustive exercise or an intravenous infusion, is associated with a worsening of attentional processes, 7 an improvement of excitability of primary motor cortex, 8 without significant modifications of spinal 9 and brainstem 10 excitability. Furthermore, experiment carried out with visual-evoked potentials 11 and somatosensory-evoked potentials 12 have shown that increases of blood lactate are associated, in both cases, with that an improvement in the conduction time between the periphery and the primary sensory areas and the worsening of intracortical communication between primary areas and additional cortical regions.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of frontal lobe functioning, elevated lactate levels seem to play a crucial, region-specific role. While some studies reported that increased lactate levels are associated with improved excitability in the primary motor cortex (Coco et al, 2010, 2014), other investigations stated contrary results for the frontal cortex as well as for brainstem and spinal cord excitability (Coco et al, 2009, 2011, 2013). Regarding the lactate uptake of the CNS from a biochemical point of view, a strong increase might lead to metabolic irritations through a decrease in pH values, which is driven by the co-transport of protons by the monocarboxylate transporter MCT1 (blood-brain barrier) as well as MCT2 and MCT4 within the CNS (Bergersen, 2015).…”
Section: Discussionmentioning
confidence: 98%